(untitled) (Journal of Computational Mathematics, 2001)
Composite Legendre-Laguerre approximation in unbounded domains is developed. Some approximation results are obtained. As an example, a composite spectral scheme is provided for the Burgers equation on the half line. The stability and convergence of proposed scheme are proved strictly. Two-dimensional exterior problems are discussed.